Study on Underwater Acoustic Sensor Network - Ming He; Qiuli Chen; Xuguang Ye; Jichuan Quan; Xiliang Chen (Dianxin kexue)
Nowadays, the study of the underwater acoustic sensor network（UASN）becomes the hotspot in the world, but there are some difficulties in controlling underwater conditions and the mobile sensor node. How to ensure the efficiency of underwater acoustic sensor networks is a major concern. Firstly, the research status and development trend of UASN were analyzed. Secondly, the hierarchical structure of the underwater acoustic sensor network was researched. Then technical challenges on the physical layer for underwater acoustic sensor network were studied. Lastly, the next research direction was pointed out.